Novel Synthesis Methods Using Phosphorus and Silicon Reagents - Thornton, Edward Alexander (2020)
Chapter one describes the synthesis and application of dioxyphosphoranes in both solution and solid phase reactions. Two novel monolithic dioxyphosphoranes were prepared and their efficacy demonstrated through the cyclodehydration of a diol. Characterisation of the monolithic reagents was performed using solid-state NMR analysis. Intermolecular amine alcohol coupling reactions, using two solution phase dioxyphosphoranes, are described and efforts to overcome competitive side reactions discussed.